PENGARUH MODEL PEMBELAJARAN SIKLUS BELAJAR EMPAT FASE TERHADAP MOTIVASI DAN KREATIVITAS MEMECAHKAN MASALAH MATEMATIKA - Sukiyanto Sukiyanto; Suparto Suparto (MEDIA DIDAKTIKA, 2018)
This study aims to train students enthusiastically in learning activities and creativity in solving mathematical problems, through collaboration or cooperation, so that students can improve their abilities to the fullest. This research is a form of mastered research, because there are two homogeneous classes that are treated, for the control class using conventional learning models and experimental classes using 4E Learning Cycle. both the control class and the experimental class, both of which sought differences regarding motivation to learn, creativity in solving mathematical problems and the relationship between motivation to learn and creativity in solving mathematical problems. The results of this study were obtained through a questionnaire for learning motivation, and a descriptive test as a measure of creativity in solving problems. the percentage of the results of the control class and the experimental class from the pretest and posttest showed that the control motivation of the control class was 70.89% and 75.85% in the experimental class 71.47% and 80.51%. Classically the experimental class has increased by 4.66% from the control class. Furthermore, the results of creativity solve the per-indicator problem through the pretest and posttest of the control class average value of 17.29 and 24.50 then for the experimental class the average value is 12.20 and 28.95. Likewise, the average value of the normal gain results for the pretest and posttest of the control classes 47.33 and 67.00, the experimental class 34.69 and 79.36 the difference in the positive increase was 12.36 from the control class.